(The effect of repeated use of cooking oil on the quality of cassava crackers) - D. Sirait, Shinta; Susilowati, Dwiningsih; K. Bunasor, Tatit (Balai Besar Industri Agro, 1995)
This research was aimed at studying the effect of repeated use of coconut oil, palm oil or soybean oil for frying cassava slices on the quality of cassava crakers produced. The statistical analysis showed that the best quality cassava crakers was produced by using fresh coconut oil.The cassava crakers produced had a moisture content of 2.01%, an oil content of 20.97%,a performance score of 3.30, a flavour score of 3.05 and a crispyness score of 2.55. The performance of cassava crakers produced by using fresh soybean oil had a highest score of 4.10 in average, where as fresh palm oil produced the most acceptable aroma and crispyness having a score of 3.30 and 4.30 respectively.In terms of taste,the highest score i.e.3.30 was acievedby using coconut oil.Â Â Â